Allochthonous and Autochthonous Halothermotolerant Bioanodes From Hypersaline Sediment and Textile Wastewater: A Promising Microbial Electrochemical Process for Energy Recovery Coupled With Real Textile Wastewater Treatment - Askri, Refka; Erable, Benjamin; Etcheverry, Luc; Saadaoui, Sirine; Neifar, Mohamed; Cherif, Ameur; Chouchane, Habib (Frontiers in Bioengineering and Biotechnology, 2020)
Textile and clothing industry is the first manufacture sector in Tunisia in terms of employment and number of enterprises. It generates large volumes of textile dyeing wastewater (TDWW) containing high concentrations of saline, alkaline and recalcitrant pollutants that could fuel tenacious and resilient electrochemically active microorganisms in bioanodes of bioelectrochemical systems. In this study a designed hybrid bacterial halothermotolerant bioanodes incorporating indigenous and exogenous bacteria from both Hypersaline Sediment of Chott El Djerid (HSCE) and TDWW is proposed for simultaneous treatment of real TDWW and anodic current generation under high salinity. For the proposed halothermotolerant bioanodes, electrical current production, chemical oxygen demand (COD) removal efficiency as well as bacterial community dynamics were monitored. All the experiments of halothermotolerant bioanodes formation have been conducted on 6 cm2 carbon felt electrodes polarized at -0.1V/SCE, inoculated with 80 % of TDWW and 20 % of HSCE for 17 days at 45°C. A reproducible current production of about 12.5± 0.2 A/m² and a total of 91 ± 3% of COD removal efficiency were experimentally validated. Metagenomic analysis demonstrated significant differences in bacterial diversity mainly at species level between anodic biofilms incorporating allochthonous and autochthonous bacteria and anodic biofilm containing only autochtonous bacteria as a control. Therefore, we concluded that these results provide for the first time a new noteworthy alternative for achieving treatment and recover energy, in the form of a high electric current, from real saline textile dyeing wastewater.